4 Change in patient-reported outcomes in patients with and without mechanical symptoms undergoing arthroscopic meniscal surgery: a prospective cohort study. (19th April 2018) - Pihl, Kenneth; Turkiewicz, Aleksandra; Englund, Martin; Lohmander, Stefan; Jørgensen, Uffe; Nissen, Nis; Schjerning, Jeppe; Thorlund, Jonas B
Abstract : Introduction: Mechanical symptoms are considered an important indication for meniscal surgery. We investigated if young (≤40 years) and older (>40 years) patients, respectively, with preoperative mechanical symptoms improved more in patient-reported outcomes after meniscal surgery than those without mechanical symptoms. Materials and methods: Patients from Knee Arthroscopy Cohort Southern Denmark (KACS) undergoing arthroscopic meniscal surgery between February 2013 and January 2015 completed online questionnaires pre-surgery, and at 12 and 52 weeks follow-up. Questionnaires included self-reported presence of mechanical symptoms (i.e. sensation of catching and/or locking) and the Knee Injury and Osteoarthritis Outcome Score (KOOS). Between-group differences in change in 4 of 5 KOOS subscales (KOOS4 ) from baseline to 52 weeks were analysed using an adjusted mixed linear model. Results: 150 young patients (mean age 31 (SD 7), 67% men) and 491 older patients (mean age 54 (SD 9), 53% men) constituted the baseline cohorts. In general, patients with mechanical symptoms had worse self-reported outcomes before surgery. At 52 weeks follow-up, young patients with preoperative mechanical symptoms had improved more in KOOS4 scores than young patients without preoperative mechanical symptoms (adjusted mean difference 10.5, 95% CI: 4.3 to 16.6), but did not exceed their absolute KOOS4 scores. No essential difference in improvement was observed between older patients with or without mechanical symptoms (adjusted mean difference 0.7, 95% CI: −2.6 to 3.9). Conclusion: Young patients (≤40 years) with preoperative mechanical symptoms experienced greater improvements after arthroscopic meniscal surgery compared to young patients without mechanical symptoms. Randomised controlled trials are needed to confirm this potential subgroup benefit.